The Impact of Environmental Performance, Environmental Costs and Company Size on Company Profitability - Ilmi, Masfufa Zuhro; Gufron, Muhammad; Putra, Muhammad Bagas; Setyorini, Umi; Rumefi, Ufi (INVENTORY: JURNAL AKUNTANSI, 2025)
This research is to analyze the impact of environmental performance, environmental costs, and company size on the profitability of companies in the Basic Materials sector listed on the IDX in 2021-2023. Profit maximization without taking the impacts of operations into account can have unfavorable impacts. Profitability is the dependent variable in this research, and the variables that are independent are environmental performance, environmental costs, and company size.  Purposive sampling produced a sample of eighteen company. Multiple linear regression analysis was performed on the data using SPSS 25. The results demonstrate that while company size has negative impacts on profitability, environmental performance and environmental costs have positive impacts.